2023
DOI: 10.18196/afkaruna.v19i1.15159
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Indonesian Millenial on Da’i: Knowledge, Presentation and Performance

Abstract: As a generation which has a unique character, the millennial generation is often percieved as a generation that is fashionable, world-accessible, and priotitizes simplicity. This study examines the perception of the millennial generation on the performance of da’i, specifically regarding knowledge capacity, presentation methods, and appearance. In addition, this study also aims to measure their perception of global influence on religious life. The current study uses both qualitative and quantitative approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The teachings of Muballighs can leave a deep impression, encouraging listeners to heed heartfelt Islamic advice and mobilizing the masses to draw closer to Allah SWT. Research conducted by Choirin et al (2023) found that there are several important indicators and variables influencing perceptions of Muballighs' performance, including demographics, religiosity, and knowledge. These indicators are crucial for Muballighs to consider when conducting preaching in middle-class communities.…”
Section: Introductionmentioning
confidence: 99%
“…The teachings of Muballighs can leave a deep impression, encouraging listeners to heed heartfelt Islamic advice and mobilizing the masses to draw closer to Allah SWT. Research conducted by Choirin et al (2023) found that there are several important indicators and variables influencing perceptions of Muballighs' performance, including demographics, religiosity, and knowledge. These indicators are crucial for Muballighs to consider when conducting preaching in middle-class communities.…”
Section: Introductionmentioning
confidence: 99%